2003
DOI: 10.1002/elan.200390115
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Oxidation of N,N‐Diethyl‐p‐Phenylenediamine in DMF and Analytical Applications. Part I: Mechanistic Study

Abstract: The electrochemical oxidation of N,N-diethyl-p-phenylenediamine in dimethylformamide has been studied at platinum and gold microdisk electrodes of various radii between 6.7 and 66 mm. The voltammetric responses revealed two electrochemically reversible waves the second of which becomes larger at higher concentrations and bigger electrode radii. The voltammetric signals have been modelled and the electrochemical oxidation reaction is not inconsistent with an EC rev ECE reaction. Kinetic parameters are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…The convergence properties of the simulation algorithm have been tested on both simulated concentration profiles and simulated coverages to ensure that the solution satisfies the accuracy requirements. [19] A grid of step size 0.1 2 (h r h z ) was found to be sufficient to achieve a convergence error of less than 1 % for all quantities of interest in less than 1 min CPU time.…”
Section: Numerical Simulation and Convergencementioning
confidence: 99%
“…The convergence properties of the simulation algorithm have been tested on both simulated concentration profiles and simulated coverages to ensure that the solution satisfies the accuracy requirements. [19] A grid of step size 0.1 2 (h r h z ) was found to be sufficient to achieve a convergence error of less than 1 % for all quantities of interest in less than 1 min CPU time.…”
Section: Numerical Simulation and Convergencementioning
confidence: 99%
“…It can be envisaged that the high boiling point of dimethylformamide (153 8C [10]) would enable the determination of sulfide under the adverse conditions of high temperature and pressure found in oil wells [5]. The voltammetric response of DEPD in DMF (0.1 M TBAP) at room temperature has been previously characterized as undergoing an EC rev ECE reaction process as depicted in Scheme 1 [11]. The nature of the electrode process in the absence of sulfide at room temperature was such that for small electrode radii of less than 100 mm and low DEPD concentrations the second oxidation wave disappears.…”
Section: Introductionmentioning
confidence: 99%
“…The results at room temperature revealed that the nature of this electrode process in the absence of sulfide is such that for small electrode radii of less than 100 mm and low DEPD concentrations the second oxidation wave disappears. Under these conditions very specific concentration ranges and electrode sizes have to be utlilized [11]. Therefore in order to improve the electrode response of the second oxidation wave at low concentrations and small electrode radii the effect of increasing the temperature of the solution on the electrode response was investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations